Intraoperative mechanical and chemical pleurodesis with 50% glucose solution for secondary spontaneous pneumothorax in patients with pulmonary emphysema - Tsukioka, Takuma; Inoue, Kiyotoshi; Oka, Hiroko; Mizuguchi, Shinjiro; Morita, Ryuhei; Nishiyama, Noritoshi (Surgery today (Tokyo, Japan), 2013)
Purpose Secondary spontaneous pneumothorax is life-threatening for patients with pulmonary emphysema. To prevent recurrence, intraoperative pleurodesis is performed in addition to bullectomy. We report the therapeutic process and effectiveness of adding mechanical plus chemical pleurodesis, with a 50 % glucose solution, to bullectomy, for patients with pulmonary emphysema-related pneumothorax. Methods The subjects were 20 patients (19 men and 1 woman; mean age 68 years) with pulmonary emphysema-related pneumothorax. After bullectomy was completed, 500 mL of a 50 % glucose solution was injected into the pleural cavity, followed by mechanical pleurodesis performed via ablation of the parietal pleura. Results The volume of pleural effusion decreased on postoperative day (POD) 1, and the temperature decreased on POD 2. The blood sugar levels increased on the day of surgery but decreased on POD 1. The mean postoperative follow-up period was 521 days. One patient died of pneumonia on POD 24. All other patients survived without pneumothorax recurrence. Conclusions These results demonstrated the effectiveness of our treatment process for pulmonary emphysema-related pneumothorax. The fact that no patient experienced pneumothorax recurrence suggests that mechanical and chemical pleurodesis with 50 % glucose solution might be effective prophylaxis.